Integration Of Local Wisdom And Islamic Entrepreneurship: Building Opportunities And Motivation For Makassar Migrants In Surabaya - Rofiqotur Riskiyah; Nur syam; Achmad Room Fitrianto (Cita konsultindo, 2025)
This study aims to examine more deeply how the Makassar ethnicity implements local wisdom values to create opportunities and motivation in entrepreneurship in accordance with Islamic teachings in the city of Surabaya. This study uses a qualitative approach with the type of ethnographic research. In this study, the data used was obtained from interviews, documentation, and in-depth observations. The results of the study show that the value of local wisdom that still exists in the Makassar ethnicity, especially in the immigrant community, is the value of siri', pacce, and reso temmangingi. This motivation was born because of the need so that the Makassar ethnicity decided to migrate or migrate to meet the needs of life, Known for its adaptability, the Makassar ethnicity is not easily influenced by the new culture that is present, including global culture, the emergence of globalization is actually used as an opportunity to develop a business, as for the form of adaptation that is carried out to adapt With the demands of the times, namely always innovating the business that is run. Islamic entrepreneurship provides an ethical framework that guides Muslim entrepreneurs in conducting business with regard to moral and social aspects. With a combination of Islamic values, local culture, and technological innovation, Makassar migrants can continue to grow and create sustainable business opportunities